Effect of current ratio, total asset turnover, and size on profitability: Evidence from Indonesia manufacturing companies - Abdul Karim; Endang Tri Widyarti; Aprih Santoso (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2023)
This study aims to look at the influence of current ratio, total asset turnover (TATO), size on profitability empirical studies in manufacturing companies listed on the IDX in 2017-2020. The sample used in this study is an empirical study on manufacturing companies listed on the IDX in 2017-2020. The population in the study was 32 manufacturing companies. The purposive sampling technique used in this study had a sample number of eighteen companies in building manufacturing with a sample of 128 data. The data analysis technique used is multiple linear regression analysis with SPSS 23 software. Data analysis begins with analyzing descriptive statistics, testing classical assumptions, testing research hypotheses. The results of the study prove that current ratio, total asset turnover, and size have a positive and significant effect on the company's Return On Assets.